Kedudukan Hukum Justice Collaborator dalam Sistem Peradilan Pidana di Indonesia - Aditya Redaya; Helvis Helvis; I Made Kantikha; Nardiman Nardiman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Justice collaborators play an important role in law enforcement. The role or function of a justice collaborator includes disclosing a criminal act or the impending occurrence of a criminal act, so that the return of assets resulting from criminal acts can be achieved to the state, providing information to law enforcement officials, providing testimony in the judicial process. The aim of this research is to analyze the legal position of justice collaborators in the criminal justice legal system in Indonesia. This research uses a type of normative juridical research by analyzing primary, secondary and tertiary legal materials. The results of the research are that the legal position of justice collaborator has a very important role in uncovering a well-organized criminal act, or a particular criminal case, so that the suspect or defendant's request to become a justice collaborator must be granted. considered based on the evidence at trial in this case. It is within the judge's authority to grant the justice collaborator's request, because this will affect the sentence. In conclusion, justice collaborators are not regulated in the criminal procedural law book in Indonesia, but are regulated in Law Number 31 of 2014 concerning Protection of Witnesses and Victims, as well as Joint Regulations for Law Enforcement Officials and Witness and Victim Protection Institutions concerning Protection of Witnesses and Victims. Complainant, Reporting Witness and Perpetrator Witness Working Together.